Advancing Microbial Electrolysis Technology via Impedance Spectroscopy and Multi-Variate Analysis - Timmerman, Lucas R.; Raghavan, Sankar; Borole, Abhijeet P. (Frontiers in Energy Research, 2022)
In this study, EIS data collected from three electrode half-cell configurations was used to qualitatively identify and quantitatively determine the responses of ohmic, kinetic, and mass transfer impedances to buffer concentration, flow rate, and applied potential in an MEC consisting of a bioanode and an abiotic nickel-mesh cathode separated by a microporous membrane. EIS measurements were collected during startup and growth (including an abiotic run) at closed circuit and open circuit conditions to accurately match portions of the EIS spectra with the corresponding physical processes and to quantify kinetic changes as the biofilm matured. Once the MEC reached a target current density of 10 A/m2, a multifactorial experimental design was executed to assess the impact of flow rate, buffer concentration, and applied voltage on EIS and performance response variables. Multivariate analysis was conducted to ascertain the relative importance of the independent variables and identify any correlations between process conditions and system response. The liquid flow through the anode was found to be strongly correlated with the impedance parameters and the MEC performance, while applied voltage influenced them to a lesser degree. The results are important from an industrial application perspective and provide insights into parameters important for process optimization.